How does Work Shape Informal Cities? - Cavalcanti, Ana Rosa Chagas (A+BE | Architecture and the Built Environment, 2019)
In this paper I will discuss the design of favelas in Brazil. The aim is mainly to highlight how labor can be used as a design tool to address social and economic phenomena shaping the ‘slum’. This will be done by analyzing the informal aspects of ‘slums,’ the rising inequality and rural-urban migration patterns in Brazil. A critical analysis of literature will be compared to empirical data that were personally acquired from Brazilian slums (Cavalcanti, 2016) during the period from 2009 until 2016. Overall, the objective will be to try and consider social aspects within a method of design. Research has shown that favelas have a different land status, different patterns of urban conglomeration and parcelling. However, when compared to formal urban planning the same logic of investment and housing commodification applies. Within favela societies, people sell, use and divide their properties according to noninstitutionalized rules, and their notion of what is shared, public or private is slightly different from that in formal urban planning environments. This leads to a greater presence of tighter, more close-knit communities. A block of houses may be a single house, with various owners sharing it (e.g. villas), the first floor of a house may be for one person and the second for another. In fact, most of the batidas de laje are made for other people (who rent the house, and thus for income generation purposes). The alleys and stairways are public spaces shared by all. Parcelling a house depends on the economic aim or need of a dweller. Finding a piece of land or a house to buy or rent depends on negotiations with the residents of a favela (Cavalcanti, 2009). The right to “verticalizing” depends on the expertise of the masons who are responsible for building the roof and/or the economic resources of the property owner. The need for shelter is considered as a way to acquire land in the outskirts of the favela. The centre is often more expensive, but still targeted by people in need for shelter. Finally, when residents move to vertical or mass housing units they repeat the social practices that they do in the favelas. With the same logic, the price of rent, land and property in favelas is consistently rising, almost proportionately with prices in the cities. Residents generally compare the prices of rent within the favela itself. In 2014, a typical house for rent in a favela (50 m2) would cost 350 Brazilian reais per month (US$106.88)10 in the city of Maceió. In general, this is practically half of what one could ask in a middle class neighborhood within Farol, a neighbourhood where a typical house for rent (50 m2), would cost circa 600 Brazilian reais per month (US$183.22).11 Such discrepancies are slightly higher amongst people who live in big metropolitan areas such as São Paulo and Rio de Janeiro, which makes it much more affordable for low-income groups to dwell in slums. In this scenario it may be observed that a capital incursion is developing within favelas: supermarket chains and products are expanding, real estate has arrived: people who received houses from the PAC (Programa de Aceleração do Crescimento) are illegally selling their tenure for higher prices (Brazil Investment Guide, 2013). Hipsters, creative classes and gringos are moving to favelas, in the process of which they contribute to the gentrification of land and goods. Apart from this, one may note that investment in hotels, museums, social activities, NGOs, UPPs (Unidades de Polícia Pacificadora) and other similar activities are constantly increasing. The aforementioned notions express the fine line between considering the favela as an idealistic, unknown dimension with an abstract logic (this is a typical way to romanticize poverty), or stating that favelas are entirely articulated with materialistic and accumulative values. Between seeing the poor as bearers of opportities versus seeing them as heroic entrepreners (Roy, 2005, 148). The difference between these two views should be highlighted and, understanding the importance of labor to residents living in slums highlights these contrasting views from their convergency and divergency, offers a new epistemological frame to study informal settlements that is able to provide a deep insight on the logics of informal settlements. The needs and patterns of favela communities have been studied by the author since 2008. The results of this paper come from an ethnographic study of the Favela Sururu de Capote in Maceió(fig. 3.1-3.2) as well as the social housing that has been conceived to shelter its removed inhabitants in light of the recent Brazilian urban challenges. This research shows how residents’ labor activities have transformed both public spaces and private homes in the favela and how practices of various scales and modes have been contributing to the distribution of urban inequalities and the growth of social informality.